Bonding to dentin as a function of air-stream temperatures for solvent evaporation - Andréia Aquino Marsiglio; Júlio César Franco Almeida; Leandro Augusto Hilgert; Paulo Henrique Perlatti D'Alpino; Fernanda Cristina Pimentel Garcia (Sociedade Brasileira de Pesquisa Odontológica, 2012)
This study evaluated the influence of solvent evaporation conditions of acid-etching adhesives. The medium dentin of thirty extracted human third molars was exposed and bonded to different types of etch-and-rinse adhesives: 1) Scotchbond Multi-Purpose (SBMP) ; water-based; 2) Adper Single Bond 2 (SB) ; ethanol/water-based, and 3) Prime & Bond 2.1 (PB) ; acetone-based. Solvents were evaporated at air-drying temperatures of 21ºC or 38ºC. Composite buildups were incrementally constructed. After storage in water for 24 h at 37ºC, the specimens were prepared for bond strength testing. Data were analyzed by two-way ANOVA and Tukey's test (5%). SBMP performed better when the solvents were evaporated at a higher temperature (p < 0.05). Higher temperatures did not affect the performance of SB or PB. Bond strength at room temperature was material-dependent, and air-drying temperatures affected bonding of the water-based, acid-etching adhesive.